Twelve‐year sarcopenia trajectories in older adults: results from a population‐based study - Caterina Trevisan; Davide Liborio Vetrano; Riccardo Calvani; Anna Picca; Anna‐Karin Welmer (Journal of Cachexia, Sarcopenia and Muscle, 2022)
Abstract Background The dynamic nature of sarcopenia, including possible transitions between its different stages, is currently unknown. We aimed to explore 12 year transitions through sarcopenia stages and identify factors associated with different sarcopenia trajectories in older adults. Methods We included 3219 participants (aged ≥60 years, 35.8% men, 96.4% community‐dwelling) from the SNAC‐K study. No sarcopenia (normal muscle strength and mass), probable sarcopenia (low muscle strength and normal muscle mass), and sarcopenia (low muscle strength and mass) were assessed at baseline and up to 12 years. Such conditions were defined based on a modified version of the EWGSOP2 criteria with muscle strength evaluated through handgrip or chair stand tests, and muscle mass from calf circumference. We estimated 1, 5, and 10 year transition probabilities through continuous‐time multistage Markov modelling. Sociodemographic, lifestyle, and medical factors associated with the likelihood of different transitions were evaluated with proportional intensity models, and the associations' strength was expressed as hazard ratio (HR) and 95% confidence interval (CI). Results Participants with no sarcopenia had 10‐year probabilities of 17.1% and 5.1% to develop probable sarcopenia and sarcopenia, and a 40.4% chance of not transitioning. Those with probable sarcopenia had similar 5‐year chances of developing sarcopenia (10.3%) and reverting to no sarcopenia (10.7%). Participants with sarcopenia had chances to revert to probable sarcopenia ranging from 8.2% (at 5 years) to 4.7% (at 10 years), and a 70.9% chance of dying after 10 years. Older age (HR = 1.11, 95% CI: 1.07–1.14), male sex (HR = 1.84, 95% CI: 1.16–2.91), current smoking (HR = 1.84, 95% CI: 1.16–2.91), and higher number of chronic diseases (HR = 1.07, 95% CI: 1.00–1.14) were associated with sarcopenia development, while higher levels of physical activity (HR = 1.84, 95% CI: 1.19–2.84) and cognitive function (HR = 1.17, 95% CI: 1.05–1.31 per each 1‐point increase in the Mini‐Mental State Examination) were associated with subsequent higher reversion rates from probable sarcopenia to no sarcopenia (P < 0.05 for all). None of the explored characteristics were associated with sarcopenia reversion to healthier stages. Conclusions Sarcopenia appears to be a dynamic condition with possible two‐way transitions between different sarcopenia stages, especially the earliest ones. Timely interventions to improve physical and cognitive function and better control individuals' chronic conditions could help counteract sarcopenia progression.